EDITORIAL BEHAVIOR SEMIOTICS ANALYSIS IN TRIBUN BONE NEWS - Qudratullah, Qudratullah (Jurnal Dakwah Tabligh, 2021)
The presence of an editorial text can be interpreted as an important thing because it gives its characteristics as well as its impression. Moving on from the explanation above, the media usually uses editorial as a propaganda material or tool which is usually aimed at certain groups or circles, to influence attitudes and behavior related to certain issues as well. Editorial policy refers to a certain segmentation of readers and the basic attitude of newspapers to determine the next step. In the scope of journalism, text editor is very important, especially in print media. Therefore, it is not just anyone who is assigned to write for the editorial. This research is qualitative research. Qualitative research aims to explain a phenomenon or object of research more broadly and completely through in-depth data collection. According to Mantra, the qualitative method is a research procedure that produces descriptive data in the form of words or words from people and observable behavior. This study uses a methodological library approach and scientifically uses a Communication Science approach. To analyze the behavior of editors in Tribun Bone news, the author uses the Roland Barthes model. The results of this research show that editorial behavior in the news reviewed in the Tribun Kota rubric in Media Tribune Bone displays media ideology that displays the sides of humanity (humanism), counter to crime and criminal behavior, morality, and gender issues.